Optimization of feed system design in family mould using mould flow simulation software - Mohd U'Kasyah, Hashim (2012)
Various problems have been found in the plastic injection industry recently.One of the major obstacles is a balancing of gates and runners in a family mold due to lack of clear understanding of the flow behavior of plastic in the mold resulting in overpacking,short shot or any other defects on the parts.The objective of this research is to to compare mould flow simulation software with actual injection molding and predict possibility of injection molding defect before injection.The aim of our analysis is to provide a simple experimental model simulation was performed.Different sizes of simple geometric parts were selected as a case study for a family mold with two cavities.Mould flow simulation software was employed to analyze the plastic feeding system such as sprues, runners and gates.The simulation results were obtained as a useful guideline for balancing of gate and runner system for a family mold.Consequently,a numerical tool simulating plastic injection processes can assist mold designers to design molds and to optimize the injection processes in order to avoid any defects such as fill time,pressure,pressure at end of fill,volumetric shrinkage,pressure at V/P switchover,temperature at flow front, sink mark index,weld lines and many more before manufacturing the molds.After get result we chose the best and compare the actual after injection.